An Approach to the Precision Parametric Reduction of Mathematical Models - Verlan, Andrey Anatolievich (Kamianets-Podilskyi National Ivan Ohiienko University, 2016)
The paper considers and analyzes an approach to simplification of mathematical models in order to substantiate possibility of accounting for limited computational resources needed to implement the models. Practical methods are proposed for application and evaluation of possible techniques of models’ parametric reduction for considered problem with obtainment of applicability criterion of the given approach